2007
DOI: 10.1063/1.2724804
|View full text |Cite
|
Sign up to set email alerts
|

A constant magnetocaloric response in FeMoCuB amorphous alloys with different Fe∕B ratios

Abstract: The magnetocaloric effect of Fe91−xMo8Cu1Bx (x=15,17,20) amorphous alloys has been studied. The temperature of the peak of magnetic entropy change can be tuned by altering the Fe∕B ratio in the alloy, without changing its magnitude, ∣ΔSMpk∣. The average contribution of the Fe atoms to ∣ΔSMpk∣ increases with increasing B content. This is correlated with the increase in the low temperature mean magnetic moment of Fe. A recently proposed master curve behavior for the magnetic entropy change is also followed by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
61
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 118 publications
(68 citation statements)
references
References 29 publications
(40 reference statements)
7
61
0
Order By: Relevance
“…Both the phenomenologically constructed universal curve for ⌬S M and field dependence power laws demonstrated that these alloys exhibited similar critical exponents at Curie temperature. With 5% Ce added to Fe 80 B 12 Cr 8 , T pk could be tuned near room temperature with relatively constant peak ⌬S M . Fe 79 B 12 Cr 8 La 1 exhibited enhanced RC compared to Gd 5 Si 2 Ge 1.…”
Section: Influence Of La and Ce Additions On The Magnetocaloric Effecmentioning
confidence: 99%
See 2 more Smart Citations
“…Both the phenomenologically constructed universal curve for ⌬S M and field dependence power laws demonstrated that these alloys exhibited similar critical exponents at Curie temperature. With 5% Ce added to Fe 80 B 12 Cr 8 , T pk could be tuned near room temperature with relatively constant peak ⌬S M . Fe 79 B 12 Cr 8 La 1 exhibited enhanced RC compared to Gd 5 Si 2 Ge 1.…”
Section: Influence Of La and Ce Additions On The Magnetocaloric Effecmentioning
confidence: 99%
“…With 5% Ce added to Fe 80 B 12 Cr 8 , T pk could be tuned near room temperature with relatively constant peak ⌬S M . Fe 79 B 12 Cr 8 La 1 exhibited enhanced RC compared to Gd 5 Si 2 Ge 1. 9 Fe 0.1 .…”
Section: Influence Of La and Ce Additions On The Magnetocaloric Effecmentioning
confidence: 99%
See 1 more Smart Citation
“…This simplification is supported by the fact that minor compositional changes-e.g., alloys from the same compositional series-do not alter the scaling behavior of their magnetocaloric effect, indicating that the critical exponents are not affected. 27,29 Once Eq. (1) is used for calculating the field and temperature dependent magnetization curves of each phase, the magnetization of the non-interacting composite can be calculated using a rule of mixtures…”
mentioning
confidence: 99%
“…In particular, there is a growing interest in studying the applicability of soft magnetic amorphous alloys as magnetic refrigerants [9][10][11][12][13][14][15][16][17][18][19][20] due to their reduced magnetic hysteresis ͑vir-tually negligible͒, higher electrical resistivity ͑which would decrease eddy current losses͒, and tunable Curie temperature T Curie . Among the different compositional series of soft magnetic amorphous alloys, Nanoperm-type alloys are those that currently exhibit the highest RC values, having also among the highest values of ͉⌬S M pk ͉.…”
mentioning
confidence: 99%